2022
DOI: 10.1101/2022.01.05.475064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation in shoot-to-root mobile transcription factor, ELONGATED HYPOCOTYL 5, leads to low nicotine levels in tobacco

Abstract: Plants have evolved complex signaling networks to regulate their growth and development. Some of these signaling components also play a crucial role in secondary metabolite biosynthesis. Among the signaling components identified to date, ELONGATED HYPOCOTYL 5 (HY5), a bZIP family transcription factor is the most investigated and known as the center of transcriptional network hub. However, HY5 has not been characterized from plants known to synthesize important secondary metabolites. In this study, based on hom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…In a previous investigation, we explored the role of the light signaling component NtHY5 in nicotine biosynthesis. Our findings unveiled the positive regulatory function of NtHY5, as mutations in HY5 resulted in a significant decrease in nicotine biosynthesis and accumulation (Singh et al, 2023). However, the involvement of other light-associated networks has not been studied as yet.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…In a previous investigation, we explored the role of the light signaling component NtHY5 in nicotine biosynthesis. Our findings unveiled the positive regulatory function of NtHY5, as mutations in HY5 resulted in a significant decrease in nicotine biosynthesis and accumulation (Singh et al, 2023). However, the involvement of other light-associated networks has not been studied as yet.…”
Section: Introductionmentioning
confidence: 64%
“…In our recent study (Singh et al, 2023), we found that NtHY5 positively regulates nicotine biosynthesis, as evidenced by lower nicotine levels in NtHY5 CR plants. Building on this, in the current study, we developed CRISPR/Cas9-based NtCOP1 mutant lines in tobacco (Supplementary Fig.…”
Section: Ntcop1 Interact With Nthy5 To Antagonistically Regulate the ...mentioning
confidence: 75%
See 3 more Smart Citations